Evaluación de la eficiencia del funcionamiento de la planta de tratamiento de aguas residuales del barrio Chimbacalle, cantón Pujilí, para la elaboración de una propuesta de rediseño en el período 2013 – 2014 - Obando Sarzosa, Stefanía Monserratte (2015)
The wastewater from Chimbacalle neighborhood of the Pujilí canton, Cotopaxi province presented higher concentrations, in the sample of the intake pipe to the plant (E) on the following parameters: turbidity, settle able solids, nitrates and solids suspended, chemical oxygen demand, biochemical demand of oxygen, in the sample well of output (S): turbidity, suspended solids, nitrates and chemical oxygen, demand biological oxygen that does not meet the maximum permissible limits according to the TULAS, Book VI, annex I, table 12. Discharges of wastewater without any treatment to bodies of fresh water or natural water channels can cause different environmental impacts that affect to the health the populations....